Intercultural Sensitivity Perceptions among Graduate Students in Indonesia and Malaysia - Trisnawati, Diana; Kamarudina, Azni Yati; Zakariaa, Abd Razak; Kumalasari, Dyah (Universitas Galuh, 2025)
The aim of this study was to measure the level of intercultural sensitivity (IS) exhibited by graduate students, explore their perceptions of IS, and analyze the strategies employed by graduate students to enhance their IS. The mixed methodologies employed to address the objectives of the study. The Intercultural Sensitivity Scale (ISS) developed by Chen and Starosta (2000) and two reflective items were included in the online questionnaire. The findings revealed there is no significant different level of IS among graduate students in Indonesia and Malaysia. The participants suggested various aspects of IS perceptions were proposed, encompassing the Perspective of Life: Acceptance, appreciation, and comprehension of cultural differences; Respect for multiple cultures; and Proficient guidance on encounters with different cultures. Multicultural educational environments within universities have the capacity to implement various strategies aimed at fostering IS among graduate students. These strategies include participation in multicultural classrooms, engagement in students' activities, cultivation of students' self-awareness, enhancement of communication skills, and provision of support services by the university